ANALISIS KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS II SD NEGERI DUREN TIGA 09 - Diah Ayu Ramadhina; Adi Putra; Petrus Suhendro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Beginning reading is the fundamental foundation in learning to read. However, in practice, many students still experience difficulties in early reading. This research focuses on identifying early reading difficulties among second-grade students at SD Negeri Duren Tiga 09, examining the factors causing these difficulties, and exploring the solutions implemented by teachers to address them. The study employs a qualitative approach and descriptive method, involving a sample of 26 second-grade students selected through purposive sampling. Data were collected using a triangulation technique, including observation, interviews, and documentation. The data analysis technique used in this study is the interactive model of data analysis (Miles & Huberman, 1994). The results show that three second-grade students at SD Negeri Duren Tiga 09 face difficulties in early reading. The difficulties include challenges in recognizing alphabet letters, distinguishing similar-looking letters, reading simple words, and hesitating when reading diphthongs. Contributing factors include a lack of stimulation and support at home, limited availability of appropriate reading materials at school, insufficient specialized teaching staff, and low student confidence and motivation in learning to read. The strategies implemented by the classroom teacher to overcome early reading difficulties include providing additional reading time, using syllable-based reading books, reading aloud assessment questions, and maintaining communication with parents.